Regeneration , Proliferation and Trans-differentiation of Adult Hepatic Oval Stem Cells into Functioning Beta-Cells and Exocrine Acinar Cells of the Pancreas in Diabetic Adult Rats - Jaumah, Zauhair A.; AL-Khafaji, Fadhil A.; AL-Khalisi, Maan H. (Journal of the Faculty of Medicine Baghdad, 2009)
Back ground: Although adult stem cells possess plasticity that permit differentiation along new lineages, production of exocrine and endocrine pancreatic cells and insulin-secreting beta-cells from adult non pancreatic stem cells has been considered controversial. We present that highly purified adult rat hepatic oval stem cells, which are capable of differentiation to hepatocytes and bile ducts epithelium, can also trans-differentiate into pancreatic exocrine-endocrine tissue, when homogenized hepatic tissue is implanted into subcutaneous tissue .Methods and Materials: A total of 60 adult Swiss albino rats were divided into two groups . Group I , control group (30 animals) was injected with normal saline into the subcutaneous and pancreatic tissue, group II (30 animals) has been exposed to 90% subtotal pancreatectomy with implantation of hepatic tissue homogenate into marked areas of subcutaneous tissue .Results: During the first three weeks the animals of group II showed both high blood glucose and serum AFP levels, then gradually started to decline and became normal around the period of six weeks and continued being normal till the end of experiment. The histological study showed regeneration and proliferation of small hepatic oval stem cells in the subcutaneous tissue around the second week and trans-differentiation of these cells into islet like cells and acinar like cells around the sixth week. Conclusions: Hepatic oval stem cell has multipotent character and can differentiate into new-lineages and formation of different clonal cells, such as islet-like cells and acinar cells of the pancreas.